A comparative analysis of feedback delivery modality within a Precision Teaching protocol to enhance drivers’ lane maintenance - Mariaelena Tagliabue; Giulia De Cet; Federico Orsini; Massimiliano Gastaldi; Riccardo Rossi (Transportation Research Interdisciplinary Perspectives)
Precision Teaching (PT) is a data-driven educational technique that continuously monitors and adjusts instruction to achieve specific, measurable learning outcomes. This research applies PT principles to train drivers in improving lane maintenance behaviour, focusing on the comparison between feedback delivery modalities, to fill a gap in prior literature due to limited and somewhat conflicting findings.This study builds upon a previous study, expanding the analysis to encompass a larger cohort of drivers and introducing a new experimental condition. Overall, 80 participants were involved in a driving simulator study in which they were asked to perform four consecutive trials, the first without feedback and others with feedback delivery.Participants were divided into three groups, each assigned to an experimental condition based on feedback administration: Auditory (A), Visual (V), and combined (VA). All systems provided contingent negative/positive feedback based on participants’ lateral position.A MANOVA was conducted, with feedback type and trials serving as independent variables. The analysis considered six dependent variables, incorporating four indicators for lane maintenance, along with two variables, mean speed and acceleration, to assess potential indirect effects.Results reveal that all tested conditions were effective. However, conditions A and VA demonstrated greater effectiveness in reducing the standard deviation of lateral position. The auditory feedback system seems to emerge as the most promising option, likely being less intrusive since it delivered fewer stimuli compared to VA. These findings could be valuable in shaping the design of PT protocols for real-time coaching programs for eco-driving or within usage-based insurance schemes.